Characterization of leakage, clamping force and retaining force of reusable sealing frame with elastomer O-ring for thin plasma polymeric coated thermoplastic polyester-ether films. (October 2021) - Scheller, Joachim; Baur, Pascal Joel
Abstract: To apply thin films to tempered injection molds, an automatable sealing solution is necessary. The study investigates the required external clamping force for a sealing frame with O-ring, which is needed to enable leak-tight closure. The clamping of thin films for different hardness of elastomer O-rings and their compression were investigated in a tensile test machine. The important parameters for a low leakage of the sealing solution were identified by defined vacuum tests. The automation capability was assessed. The study revealed that high external clamping forces and low leakages are majorly dependent on high compression and high hardness of the O-ring. This results in a contact pressure, which is the primary criteria for the sealing performance of O-rings with a hardness of 15–75 Shore A. The results show that thin films made of thermoplastic polyester-ether tear in the tensile test at low compressions if the hardness of the O-ring exceeds 60 Shore A. Tearing occurs at lower compressions than needed for a sufficient sealing performance. Therefore, the choice of the O-ring and the dimension of the groove need to be based on the required sealing performance of the sealing frame and not on the fixture of thin films. Highlights: High hardness/compression and low diameter of O-ring result in gas-tightness. Retaining force is determined by coupling's surface, O-ring, and its compression. High depth of O-ring's groove can decrease forces at sufficient sealing performance. Dimension of sealing frame should be based on sealing, not on fixture of thin films.